Demographic and clinical characteristics of Guillain-Barré syndrome at Kenyatta National Hospital, Kenya - Stephen Kivuva Muindi; Mohamed Onyango; Moses Muia Masika (BMJ Neurology Open)
Background Guillain-Barré Syndrome (GBS) is a life-threatening neurological disorder with limited data from sub-Saharan Africa. This study describes the clinical features, outcomes and predictors of mortality among GBS patients at Kenyatta National Hospital in Nairobi, Kenya.Methods This cross-sectional study used retrospective data from patient files obtained from the Health Information Department from 2014 to 2023 on 207 GBS patients. A census of all available patient files meeting inclusion criteria was done. Demographic and clinical data were collected; descriptive and correlation analyses were performed using IBM SPSS Statistics V.25.0.Results The male to female ratio was 1.01:1. The median age was 21 years. A quarter of cases were in the 0–5 years age group. HIV and hypertension were the most common comorbidities, particularly in females. Clinical manifestations included hyporeflexia, hypotonia and sensory loss. Significant morbidity was observed, with 25.7% experiencing respiratory complications and 35.4% requiring intensive care. Female patients had increased mortality risk (adjusted OR (aOR)=4.03, 95% CI: 1.15 to 14.11, p=0.029). HIV-positive females had over sevenfold higher odds of death (aOR 7.21, 95% CI: 1.56 to 33.36, p=0.011), while intravenous immunoglobulin (IVIg) use reduced mortality by 75% (aOR 0.25, 95% CI: 0.08 to 0.85, p=0.026).Conclusion This study highlights GBS’s demographic, clinical and outcome aspects in Kenya. GBS predominates in young individuals. Females experience higher comorbidity and mortality rates. Improving access to IVIg, intensive care unit and early supportive management is essential. Further research is needed to explore gender-based mortality differences and age-related morbidity variations.